Triple monoclonal protein-related kidney lesions in a patient with plasma cell dyscrasia: a case report - Alvi, Arsalan; Gallan, Alexander J.; Klomjit, Nattawat (Frontiers in Nephrology, 2024)
A toxic monoclonal protein typically results in a single kidney pathology due to the specific biophysical characteristics of monoclonal proteins. Multiple monoclonal protein lesions are rarely reported and often portend a poor prognosis. We present a 57-year-old male who developed rapidly progressive glomerulonephritis after concealed ruptured diverticulitis. A kidney biopsy showed light chain cast nephropathy, light chain proximal tubulopathy, and thrombotic microangiopathy. Laboratories showed IgG kappa with an M-spike of 0.2 g/dl and a kappa light chain of 16 mg/dl. A bone marrow biopsy showed 3% kappa-restricted plasma cells. The dramatic renal presentation despite the minimal hematological burden is suggestive of a highly toxic light chain, which is consistent with monoclonal gammopathy of renal significance (MGRS). Clone-directed therapy and a complement blockade were initiated. The patient remained dialysis-dependent despite a hematological response. This case highlights the importance of considering the toxic properties of monoclonal proteins in causing kidney diseases. Our case is the first report of an MGRS patient with three distinct kidney lesions. Triple monoclonal protein-related kidney lesions are very rare and are usually associated with multiple myeloma. Light chain cast nephropathy (LCCN) is a myeloma-defining event but his light chain (LC) (<50 mg/dl) and plasma cell (<10%) burdens were low which makes this case very unusual. Sepsis-induced low-flow stage and the toxic properties of LC may induce LCCN in this patient. Aggressive therapy is likely needed to eradicate the clone in order to achieve an organ response.